Why aren't more patients with breast cancer enrolled in clinical trials?. Issue 28 (1st October 2022) - Lalor, Fallon; Caston, Nicole E.; Ingram, Stacey A.; Wan, Clara; Sussell, Jesse; Patel, Shilpen A.
Abstract : 84 Background: Only 2-8% of adult patients with cancer participate in clinical trials, likely due to strict exclusion criteria as well as financial and access issues. The primary objective of this study is to understand the population of patients with breast cancer who are and are not offered a clinical trial and the impact of exclusion criteria on enrollment. Methods: Inclusion and exclusion criteria from study protocols housed in OnCore and ClinicalTrials.gov were obtained for breast cancer-specific, therapeutic clinical trials open at the University of Alabama at Birmingham (UAB) from 2016 to 2020. Patients with breast cancer receiving oncology services at UAB from 2016 to 2020 were identified from electronic health records. Race and ethnicity and address were abstracted. Address was utilized to characterize patients as living in areas of higher vs. lower deprivation (Area Deprivation Index) and rural communities (Rural-Urban Commuting Area). Chart abstraction was conducted to assess if patients were offered a trial, eligible for a trial, reason for ineligibility, and enrollment in trial vs standard of care treatment. Results: 518 patients were included; 387 were offered a trial and 131 were not. The median age of patients offered a trial was 57 years old, whereas the median age of patients who were not offered a trial was 61. The majority of patients offered a trial were more often White (72% vs. 24% African American), resided in areas of lower disadvantage (70% vs 17% most disadvantaged), and urban residents (75% vs 13% rural). Of the 387 patients offered a trial, 319 (82%) enrolled, 34 (9%) declined enrollment and chose standard of care, and the remaining 34 (9%) were interested in enrollment but later found to be ineligible. Reasons for ineligibility of the 34 patients who were offered a trial included comorbidities (n = 9), tumor size (n = 7), metastases (n = 5), and previous cancer history (n = 4). Additionally, 9 patients were ineligible for miscellaneous reasons (abnormal labs, age, prescription, trial closed to accrual, tumor characteristics). Of the 131 patients that were not offered a clinical trial, 77 (59%) were ineligible for enrollment. Reasons for ineligibility included: stage 1 disease (n = 35), tumor size and characteristics (n = 24), and comorbidities and abnormal labs (n = 18). The remaining 54 patients would have been eligible, but their provider did not offer a clinical trial. Conclusions: Most patients who are offered a clinical trial are willing to participate; physicians not offering a trial to patients appears to be a driver for low enrollment. Strict exclusion criteria related to comorbidities limit trial participation. Further work is needed to understand the relative importance of these eligibility criteria in relation to validity. Efforts should be made to include patients in clinical trials that reflect the diverse patient population that will receive the drug in the future.